(untitled) (Jurnal Teknologi (Sciences & Engineering), 2021)
LM6-aluminum alloy based-metal matrix composites (MMC) reinforced with Al2O3 ceramic particles were fabricated through stir casting. Al2O3 particles with different weight content (5, 10, and 15%) were dispersed into the LM6 Al-Si alloy. The macro and microstructures, mechanical properties, fracture surface, hardness, and impact toughness of the resulted MMCs together with the plain LM6 alloy were evaluated. The results showed that the added 5 wt.% Al2O3 was distributed homogenously with good wettability. The addition of Al2O3 refined the constituents of the LM6 alloy; Al-Si dendrites and the α-Al grains. At 10 wt.% Al2O3, some localized clusters appeared with some granular cracks. Increasing the Al2O3 addition to 15 wt.% resulted in particle agglomerations with multiple cracks and porosity. Both the tensile strength and the 0.2 % proof strength of the produced MMCs were improved up to 10 wt.% Al2O3 and then reduced. The fracture surface of 5 wt.% MMC was brittle-ductile mixed-mode fracture dominated by brittle fracture. The other percentages were almost brittle fracture. The hardness of the produced MMCs was remarkably improved. The hardness value reaches to about 86 HV at 10 wt. % Al2O3 addition. The impact toughness of the resulted composite materials was decreased notably at higher addition of Al2O3.